An Elective Course in Personal Finance for Health Care Professionals - Chui, Michelle A. (American Journal of Pharmaceutical Education, 2009)
OBJECTIVES: To create, implement, and assess an elective course on the principles and applications of personal finance. DESIGN: A 1.5 unit (15 hours total) elective course was designed using active-learning pedagogy, lecture, and group discussion. Homework assignments were designed to provide practical tools and materials that students could individualize and apply to their personal financial goals. ASSESSMENT: Student satisfaction, using a standard course evaluation form, revealed consistent high ratings. Student enrollment increased from 19 students in its initial year to 90 students in its fourth year. Student knowledge, assessed using the Jump$tart Financial Literacy Survey, indicated significant knowledge acquisition. CONCLUSION: Many pharmacy students are ill equipped to effectively handle the complex financial decisions they face after graduation. This course provides students with practical tools to identify appropriate ways to achieve their financial goals and critically evaluate financial advice and advisors.